Multi-Part Tariffs and Differentiated Commodity Taxation - Anna D'Annunzio; Mohammed Mardan; Antonio Russo (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study commodity taxation in markets where firms, such as Internet Service Providers, energy suppliers and payment card platforms, adopt multi-part tariffs. We show that ad valorem taxes can correct underprovision and hence increase welfare, provided the government applies differentiated tax rates to the usage and access parts of the tariff. We obtain this result in different settings, including vertically interlinked markets, markets where firms adopt menus of tariffs to screen consumers and where they compete with multi-part tariffs. Our results suggest that exempting these markets from taxation may be inefficient.
Keywords: D42; D61; H21; 330; commodity taxation; multi-part tariffs; price discrimination